Reusable Palladium Nanoparticles Catalyzed Oxime Ether Directed Mono Ortho‐Hydroxylation under Phosphine Free Neutral Condition. Issue 3 (29th November 2018) - Saha, Rajib; Perveen, Naziya; Nihesh, Naorem; Sekar, Govindasamy
Abstract: An efficient, reusable and stable binaphthyl stabilized Pd‐nanoparticles (Pd‐BNP) catalyzed the direct ortho ‐C−H hydroxylation of acetophenone oxime ethers under neutral and phosphine ligand‐free condition has been developed. A readily available, economic, safe and greener oxidant oxone has been used in this direct ortho ‐hydroxylation. The scope of the reaction has been studied with various acetophenone oxime ethers including electron rich to electron deficient system and the reaction afforded only mono hydroxylated products in a highly regioselective manner. Several control experiment results confirmed that the oxone is the hydroxyl source. The Pd‐BNP catalyst has been reused up to five times. The heterogeneous test confirmed that the reaction is catalyzed by the heterogeneous Pd‐BNP catalyst. Abstract :